Decolonising management education: An empirical study - Nukunah, Chimene; Eccles, Neil (Critical Studies in Teaching and Learning, 2024)
Conversations in South Africa around decolonising higher education since the 2015/2016 #RhodesMustFall movements have remained largely theoretical. Recently, much of the attention in many higher education institutions seems to have moved on from these conversations to apparently more ‘interesting’ topics like the fourth industrial revolution and the impact of Covid-19. The aim of this article is to rekindle the desire among participants in higher education, specifically in management education, to respond in a practical manner to the call for decoloniality. Towards this aim, we present findings from a constructivist grounded theory study in which we interviewed 31 participants in the management education space on how to decolonise management education. We describe the following six themes that emerged: ‘globalisation’, ‘race’, ‘capitalism’, ‘meaning of decolonisation’, ‘lekgotla’, and ‘critical pedagogy’. Drawing on these themes we propose a tentative conceptual framework on how we might begin to construct a meaningful decoloniality movement in the context of management education.